Exploration of Factors Affecting Consumer Perceptions of Advertisements Generated by Artificial Intelligence - Noventa, Oscar Chrismadian; Widjojo, Maria Rosa Ratna Sri Anggraeni; Putranta, Martius Parnawa (Research Horizon, 2026)
This study examines the growing role of generative Artificial Intelligence (AI) in advertising, particularly as AI-generated content becomes increasingly embedded in everyday digital consumption. While prior research has produced mixed findings regarding consumer responses to AI-generated advertisements, the underlying psychological mechanisms driving acceptance remain insufficiently understood. Accordingly, this study aims to investigate how visual characteristics of AI-generated advertisements influence consumer acceptance through perceived intelligence. A quantitative survey was conducted among 415 respondents in Yogyakarta who had prior exposure to AI-generated advertisements. The study analyzes the effects of perceived realism, vitality, imagination, and synthesis on perceived intelligence, as well as its subsequent impact on willingness to accept. Data were analyzed using factor analysis and hypothesis testing. The findings reveal that perceived realism, vitality, and especially imagination positively influence perceived intelligence, with imagination emerging as the strongest predictor. Contrary to expectations, synthesis also shows a positive effect. Furthermore, perceived intelligence significantly enhances willingness to accept AI-generated advertising. In conclusion, consumer acceptance is driven not only by technological novelty but by the perceived quality, creativity, and coherence of AI-generated content.